(untitled) (Journal of Fatima Jinnah Medical University, 2025)
Methods: This experimental study was done in Combined Military Hospital Lahore and Fatima Jinnah Medical University over 18 months. Isolated tissues obtained from adult healthy rabbits and rats were used in the study. Sample size was calculated by OpenEPI formula. Animals were divided into 5 groups comprising 20 animals in each group. Strips of rabbit ileum and rat gastric fundus tissues were allowed to stand in an organ bath with an isotonic force transducer attached to powerlab (AD instruments). Increasing concentrations of serotonin, mosapride, and ondansetron were applied to tissues and their responses were recorded by the change in the mean force of contraction (grams). Increasing concentrations of serotonin and mosapride were administered in the presence of ondansetron and their responses were recorded. T-test was and ANOVA followed by Post Hoc Tukey’s test were used for statistical analysis. Results: There was a dose-dependent increase in the mean force of contraction with Serotonin, mosparide and ondansetron on rabbit ileum and rat gastric fundus tissue. Increasing concentration of mosparide in the presence of ondansetron also showed a dose-dependent increase in response as depicted by the change in the mean force of contraction in grams. Conclusion: Mosapride has less stimulatory effect on gastrointestinal tissue as compared to when used in combination with ondansetron.